O “significado" do feminismo negro - Silva, Bianca Pereira da (Universidade Federal do Tocantins, 2023)
This paper proposes a critique about the unfeasibility of the history of black women in Brazil, and about the organizational ideas that have different spaces. It is the resistance of these women in the search for their own historical protagonist, which has already faced and still faces many challenges in the socio-cultural combat of a racist, sexist, sexist country, and that very much attacks and kills black women. In the enslaved period there was a massacre to black women, and today in a veiled way they withdraw these women from their spaces by privileging white women, denying us what is ours. As part of the quest to understand the processes, this paper aims to show how black women struggled within social movements, from the historical period unknown by literature, which hides the importance and especially the real role of these women. women in the social historical construction of this country until the present day, listing their guidelines aimed at combating racism, sexism and violence against black women. With this, its trajectory of the last thirty years of mobilizations organized in all the regions of the country, from the context in which the processes were beginning in 1988 with the first meetings, until the National Meeting of Black Women; which occurred 30 years later, in the year 2018.